Variation of kelulut (Heterotrigona itama) habitat landscapes in South Kalimantan. Issue 1 (November 2021) - Wahyuningtyas, R S; Halwany, W; Siswadi, S; Hakim, S S; Rahmanto, B; Lestari, F; Basiang, H A; Alamsyah, M S; Susianto, A; Buwono, D C; Suryanto, E; Effendy, M; et al.
Abstract: Honey production depends on the availability of the landscape as a habitat for producing bee's food sources. The purpose of this study was to determine different landscapes as a habitat for kelulut ( Heterotrigona itama ) bees in producing honey from 5 different stingless bee locations. The research was conducted in three districts: Hulu Sungai Tengah, Hulu Sungai Selatan and Tapin District, South Kalimantan Province. This research was conducted to record the types of vegetation in each landscape, which can be divided into three categories; 1 location was a combination type of forest and garden (type 1), 2 locations was a combination type of settlement, shrub, and paddy fields (type 2), and 1 location was a combination type of settlement, plantation, and shrub (type 3). Each meliponiculture also recorded the honey production every month. The results showed that the farmers' number of beehives was between 96 and 252 hives/farmer. The average production in the rainy season is 0.17 L hive- 1 year −1, and the dry season is 0.24 L hive −1 year −1 . Honey production per year for each location was as follows: location type 1 produces 1.59 L hive −1, location type 2 produces 1.85 L hive −1, and location type 3 produces 2.41 L hive −1 . Plant identification results at each type of location showed that the number of species found at vegetation cover type 1, 2, and 3 was 116, 128, and 107 species, respectively. At the farms with vegetation cover types 2 and 3, many different flowering shrubs provide year-round forage for the stingless bee.